STUDI FAKTOR-FAKTOR PENYEBAB KEMISKINAN MASYARAKAT DESA LOHIA KECAMATAN LOHIA KABUPATEN MUNA - Sartika, Cica; Balaka, M.Yani; Rumbia, Wali Aya (JURNAL EKONOMI UHO, 2016)
This study aims to find out the characteristic poor poeple in Lohia Village, Muna Regency. Data used is primary and secondary data. Primary data collected through questionare from 45 respondent. Respondent is determined by purposive sampling based on homogen characteristic. Data analyzed with descriptive. The results show that poor poeple in Lohia Village is characterized by: productive age, the higer number of family members, the lower education and skill, lower income, lack of production factors and the lower of work ethic.